Ideological adapting of orthodox vocabulary in soviet and post-soviet dictionaries - Mikhailova, Olga; Mikhailova, Yulia (Przegląd Wschodnioeuropejski, 2018)
The article is devoted to the analysis of vocabulary definitions that explain the vocabulary of Orthodoxy. The material was the basic dictionaries published in the USSR, modern explanatory dictionaries of the Russian literary language and dictionaries that represent the religious picture of the world. It is shown how by means of ways of interpretation of orthodox lexicon, system of marks and illustrations in dictionaries of the Soviet period occurs ideologization of lexicon, polarization of evaluations, opposition of Orthodox religion. Explanatory dictionaries of modern times are exempted from the Soviet ideological evaluations and political characteristics. They overcome ideological simplification in the representation of religious vocabulary. As a result of comparative analysis of vocabularies for secular people and dictionaries for the religious sphere discourse variants of vocabulary are revealed and it is proved that differences in the definitions of identical Orthodox lexemes are conditioned by the ideological concept of dictionaries compilers.